2017
DOI: 10.1111/1467-9604.12169
|View full text |Cite
|
Sign up to set email alerts
|

‘You have to be like everyone else’: Support for students with vision impairment in mainstream secondary schools

Abstract: The experiences of seven Australian senior secondary school students with vision impairment attending mainstream schools in Victoria were explored to gain an understanding of the support mechanisms operating to allow them access to an inclusive education. This qualitative study primarily used the indepth interviews of students, augmented by brief interviews with Heads of Education Support, parents, aides and teachers. Students attributed difficulties to time available, accessing e-print and large format materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 42 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…It is clearly indicated that general education teachers do not have adequate skills and knowledge to include students with VI and they need to be informed about instructional adaptations, such as converted maps, charts, and graphs which foster tactile learning and printed materials with a larger font size. Furthermore, teachers should receive training on mobility and orientation, which enables students to move safely in school settings (Cox & Dykes, 2001;Kalloniatis & Johnston, 1994;Opie, Deppeler, & Southcott, 2017). Students with VI can be successful in mathematics with appropriate adopted materials and teaching strategies in inclusive settings along with qualified teachers (Asamoah et al, 2018;Klingenberg et al, 2019;Koehler & Wild, 2019;Rule, Stefanich, Boody, & Peiffer, 2011;Teke & Sözbir, 2019).…”
Section: Results Discussion and Suggestionsmentioning
confidence: 99%
“…It is clearly indicated that general education teachers do not have adequate skills and knowledge to include students with VI and they need to be informed about instructional adaptations, such as converted maps, charts, and graphs which foster tactile learning and printed materials with a larger font size. Furthermore, teachers should receive training on mobility and orientation, which enables students to move safely in school settings (Cox & Dykes, 2001;Kalloniatis & Johnston, 1994;Opie, Deppeler, & Southcott, 2017). Students with VI can be successful in mathematics with appropriate adopted materials and teaching strategies in inclusive settings along with qualified teachers (Asamoah et al, 2018;Klingenberg et al, 2019;Koehler & Wild, 2019;Rule, Stefanich, Boody, & Peiffer, 2011;Teke & Sözbir, 2019).…”
Section: Results Discussion and Suggestionsmentioning
confidence: 99%
“…This finding supports those of previous studies. For instance, Opie, Deppeler, and Southcott [15] and West et al [41] clarified that barriers in accessing the curriculum were experienced more in high schools than in primary schools, and were more prevalent in subjects such as Mathematics, Science, and Physical Education. Interestingly, this situation was documented by research studies in countries including the U.S., Australia, Canada, and Singapore, as well as on the African continent, indicating that it may be a universal issue [1].…”
Section: Overview Of Findingsmentioning
confidence: 99%
“…Students were convened in a specialized environment that met their needs, with continuous support from qualified teachers for the visually impaired [13]. With inclusive education, although students are educated in their local communities, they are often placed in a learning environment that relies heavily on vision, with a limited presence of teachers qualified to support the visually impaired [14,15].…”
Section: Introductionmentioning
confidence: 99%